The impact of various staining substances and immersion time on the stainability of bonded sapphire brackets with three kinds of light cure orthodontic adhesives (An in-vitro study) - Albo Hassan , Alaa F; Ghaib , Nidhal H (Journal of Baghdad College of Dentistry, 2020)
Background: The need of the patient for a more reasonable esthetic orthodontic intervention has risen nowadays. Thus, orthodontists make use of esthetic orthodontic materials like brackets, ligature elastics, and arch wires. The esthetic brackets come as different forms of materials, such as ceramic brackets, which have their stainability remaining as the most important consideration for the patients and the orthodontists. This study aimed to compare the staining effects of various staining materials, including black tea, cigarette smoke and Pepsi, as well as the time effect on the color stability of sapphire ceramic brackets bonded with three kinds of light cure orthodontic adhesives: Transbond, Resilience and Enlight. Materials and Methods: Three hundred sixty sapphire brackets were utilized and divided into three different groups (120 brackets per group) based on the type of bonding material. Each group was further subdivided into four subgroups (30 brackets each) based on the media in which the brackets were fully immersed, including distilled water, black tea, cigarette smoke and Pepsi. Moreover, each of these subgroups were further subdivided, based on the time of immersion relative to each media, into 3 different smaller subgroups (10 brackets each): one day, 7 days and 14 days with incubation at 37Â°C. A UV-visible type of spectrophotometer was utilized in order to perform a light absorption test. ANOVA and post hoc LSD tests were used for comparison. Results: The smoke of cigarette appeared to be the highest potent staining type among the tested materials followed by Pepsi and tea. The staining effects of all kinds of staining materials in relation to the bonded brackets color with all adhesive types were raised with increased time of immersion. Conclusion: The patientâ€™s cooperation and habits should be taken into consideration when using sapphire orthodontic brackets. In addition, the patients should be instructed to decrease the consumption of staining beverages. Keywords: Stainability, staining materials, sapphire brackets.